We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
106
3
avatar
y – x = 14 x = 4y – 2
 Apr 23, 2019
 #1
avatar+1069 
+2

Substitute second equation into the first one

 

y-(4y-2)=14

 

-3y-2=14

 

-3y=16

 

y=-16/3

Now substitute back

x=-70/3

 Apr 23, 2019
 #3
avatar+44 
-6

When you did that, you were supposed to change the 2's symbol since there was a subtraction sign in front of the parentheses getting -3y+2=16

doorknoob  Apr 23, 2019
 #2
avatar+44 
-6

The first person who replied used substitution (and did it wrong), but here is it in elimination form and substitution

So in this problem it would be easier to substitute since it already gives us x

y-x=14

x=4y-2

To substitute it we can do y-(4y-2)=14

To get y = -4

We can then plug it into the X equation to get

x = -18

So the answer above is wrong

We can multiply the first sentence by 4 to get

4y-4x=56

We can then get the two equations:

4y-4x=56

4y-2=x

Then we can subtract these two equations from each other the eliminate the y.

 Apr 23, 2019

10 Online Users